Using The Rose Bengal Plate Test to Diagnosis Contagious Abortion (Brucellosis) in Aborted Ewes in Al-Muthanna Province - Tawfeeq Abd, Muna (Central Asian Journal of Medical and Natural Science, 2025)
Along with being a zoonotic disease that is spread to humans, the purpose of the presented work was determining the prevalence regarding brucellosis, which results in recurrent abortions in ewes in the province of Al-Muthanna based on the Rose Bengal plate test (RBPT). This has been done for controlling the disease and lessen the resulting financial losses. Serum samples from 40 ewes have been gathered in various parts of the province of Al-Muthanna between February and April 2024, throughout the lambing season. With the use of RBPT, the data indicate that 45% of ewes have brucellosis (18/40). According to the research, the percentage of ewes infected with Brucella throughout the lambing season was high, and there was a highly significant correlation between the two variables. The animal’s symptoms, case history, and the abortion time—which occurs following the third month of pregnancy—were all factors in the diagnosis. Since the germs grow and multiply in the case when they reach the reproductive system, particularly in uterine placentomes, which causes them to suppurate and separate the fetus from its dam, resulting in abortion, along with the clinical signs regarding brucellosis, retained placenta, arthritis, mastitis, corneal inflammation, laterals, or bilateral orchitic in rams, we can confirm that the cause of abortion is mechanical rather than toxic. According to our findings, RBPT is a screening test utilized for identifying the prevalence of Brucella species in serum samples. Ewes in this area have been found to be infected with Brucella, necessitating additional investigation and research into additional risk factors linked to isolation and infection of Brucella in this region.